Association between V̇O2max, handgrip strength, and musculoskeletal pain among construction and health care workers - Lene Lehmann Moberg; Lars-Kristian Lunde; Markus Koch; Anne Therese Tveter; Kaj Bo Veiersted (BMC Public Health, 2017)
Abstract Background Construction and health care workers have a high prevalence of musculoskeletal disorders, and they are assumed to have physically demanding jobs. Profession- and gender-specific associations between individual capacity and musculoskeletal pain have not been sufficiently investigated. The main aim of this study was to examine the association between individual capacity (maximal oxygen uptake (V̇O2max) and handgrip strength) and musculoskeletal pain among construction and health care workers. Methods This cross-sectional study examined 137 construction and health care workers (58 women and 79 men) with a mean age of 41.8 years (standard deviation 12). Aerobic capacity was indirectly assessed by the Åstrand cycle test, and strength was assessed by a handgrip test. Musculoskeletal pain was described by total pain, divided into neck, shoulder, and low back pain, during the last 12 months, and it was dichotomized in below or above 30 days. Logistic regression was used to analyse the associations between V̇O2max, strength, and musculoskeletal pain in the total study sample and separately for construction and health care workers. Analyses were adjusted for age, gender, body mass index (BMI), and selected mechanical and psychosocial factors. Results Every second participant (51.8%) reported pain in either neck, shoulders or low back for more than 30 days during the last 12 months. Among the health care workers, a small but significant association was found between a high V̇O2max, high handgrip strength, and a low level of musculoskeletal pain. No association was found for the construction workers. Conclusions An association between V̇O2max, handgrip strength, and musculoskeletal pain was found for health care workers but not for construction workers. These results indicate that activities promoting individual capacity may reduce musculoskeletal pain for health care workers.